Controlled release of gallium maltolate complex from injectable phosphocalcic cements. (1st September 2022) - Dupleichs, Manon; Limelette, Maxence; Mellier, Charlotte; Montouillout, Valérie; Lefevre, François-Xavier; Quillard, Sophie; Mevellec, Jean-Yves; Janvier, Pascal
Abstract: Some cancers have tropism for bone: breast, prostate, lung, kidney, and thyroid cancers are the most common. Bone metastases can be treated with surgical resection and the resulting bone defects can be filled with injectable biomaterials. Among these, calcium phosphates may be the biomaterials of choice because of their ability to locally release anticancer active ingredients. Herein, we propose the synthesis of injectable calcium phosphate cement (CPC) loaded with gallium maltolate (GaM). It is an extremely promising anticancer drug with also antibiotic and anti-inflammatory properties. This synthesis was based on commercial cement whose main component was α -tri-calcium phosphate ( α -TCP), and the final product obtained after hardening was calcium-deficient apatite (CDA). Two formulations were prepared, containing 3.5% and 7% by mass of GaM (CPC-3.5G and CPC-7G respectively). Powder x-ray diffraction (pXRD), Fourier transform infrared (FTIR) spectroscopy, and magic-angle spinning nuclear magnetic resonance (NMR MAS) 31 P analyses showed that the direct incorporation of GaM did not modify the final cement composition. Textural properties, such as setting time, injectability, workability, and cohesiveness, were well preserved or even improved. Additionally, the mechanical strength, although slightly reduced, remained perfectly compatible with surgical use. In vitro kinetics studies of GaM-loaded CPCs showed a controlled release of GaM (49% at 60 days for CPC-3.5G and 58% at 116 days for CPC-7G) following Fick's law. Raman imaging was used to visualize its diffusion within the cement during in vitro release experiments. Finally, the structural integrity of the gallium complex in the CPC was confirmed using NMR MAS 71 Ga.